Cell size trade‐offs govern light exploitation strategies in marine phytoplankton - Tim Key; Avery McCarthy; Douglas A. Campbell; Christophe Six; Suzanne Roy; Zoe V. Finkel (Environmental Microbiology, 2010)
Summary Marine phytoplankton show complex community structures and biogeographic distributions, the net results of physiological and ecological trade‐offs of species responses to fluctuating, heterogeneous environments. We analysed photosynthesis, responses to variable light and macromolecular allocations across a size panel of marine centric diatoms. The diatoms have strong capacities to withstand and exploit fluctuating light, when compared with picophytoplankton. Within marine diatoms, small species show larger effective cross‐sections for photochemistry, and fast metabolic repair of photosystem II after photoinactivation. In contrast, large diatoms show lower susceptibility to photoinactivation, and therefore incur lower costs to endure short‐term exposures to high light, especially under conditions that limit metabolic rates. This size scaling of key photophysiological parameters thus helps explain the relative competitive advantages of larger versus smaller species under different environmental regimes, with implications for the function of the biogenic carbon pump. These results provide a mechanistic framework to explain and predict shifts in marine phytoplankton community size structure with changes in surface irradiance and mixed layer depth.